EVALUASI TINGKAT PENERIMAAN APLIKASI DATA POKOK PENDIDIKAN (DAPODIK) MENGGUNAKAN METODE TECHNOLOGY ACCEPTANCE MODEL (TAM) (Studi Kasus : Pemutakhiran Data PIP Menggunakan Aplikasi DAPODIK) - Aryanto Aryanto (JURNAL FASILKOM (teknologi inFormASi dan ILmu KOMputer), 2019)
ABSTRACT Smart Indonesia Program (PIP) is a direct cash assistance provided to underprivileged students with Smart Indonesia Card (KIP) as a marker / identity to ensure and ensure that children get the assistance of the Smart Indonesia Program. In order to monitor the distribution of KIP and to ensure that KIP has been accepted and can be utilized by the students, the Ministry of Education and Culture shall validate and update KIP recipient data through the Dapodik Application. Dapodik is an online and real time, based application that can be accessed and operated directly by all school operators in data entry, data processing, updating of PIP data, education personnel, students, periodic, sanitation, study groups and data of infrastructure school. This study aimed to evaluate the level of acceptance of basic education data applications (dapodik) using the method of Technology Acceptance Model (TAM). This study used 3 modified variables are Perceived Ease of Use (PEOU) and Perceived Usefulness (PU) as independent variable while Acceptance of IT as dependent variable. This study used simple random sampling as a sampling technique, with the number of respondents as many as 66 people operators. For data analysis techniques, this study used multiple regression techniques with descriptive quantitative research types, as well as data processing tools using SPSS 16.00 for windows software. The results showed that the benefit factor (Perceived Ease of Use) of 43.5%, factor amenity (Perceived Usefulness) of 36.8%. This proves that the more dominant benefit factor influences receipt of Dapodik application usage as PIP data updating application. Key Words: Aplication of Dapodik, Perceived Ease of Use, Perceived Usefulness, Perceived Usefulness, Acceptance of IT, Technology Accaptance Mod